Mapear para aprender: uso de mapas conceituais e de mapas mentais como recurso de aprendizagem ativa no ensino de Biologia - MIRANDA, Ana Telma da Silva (2021)
The word proptoses Thé use o Conceptual Maps (MC) and Mental Maps (MM) in Thé teaching o Biology. Its main objective is to analyze Thé use o such resources as facilitators for active learning by students in high school biology classes. It is characterized as a research with a qualitative approach, o a case study typology, with data collection procedures that included Thé maps produced and questionnaires answered by Thé students. The research was carried out in person in a high school class at Thé IFMA (Federal Institute o Education, Science and Technology o Maranhão), with thirty-eight students. The organization and treatment o Thé collected data is divided into two stages. In Thé first, a characterization o Thé maps produced was carried out, based on specific literature on Thé subject, with authors such as Tony Buzan (2019) creator o Mental Maps and Joseph Novak (1998) creator o Concept Maps. In Thé second stage, to analyze Thé data from Thé questionnaires, Thé framework o content analysis by Bardin (2006) was used. The theoretical foundation o this research was based on Thé Theory o Meaningful Learning (AUSUBEL, 1982; MOREIRA, 2012), on Thé cognitive processes involved in mental mapping (BUZAN, 2019), on conceptual mapping (AGUIAR, CORREIA, 2013; TAVARES, 2007) and other contemporary authors who study Thé use o maps in teaching and learning processes (DAVIES, 2011; MARQUES, 2008). The survey results revealed that Thé participants perceived Thé maps as resources that helped in Thé organization o information, facilitated understanding, memorization, and stimulated learning mainly about Biology content, which contains many scientific terms. Participants also pointed out their difficulties in Thé elaboration o concept maps and preferences for mental mapping. As an educational product, an ebook was developed for Biology teachers, about Thé characteristics and differences between Mind Maps and Conceptual Maps, ways o elaboration and suggestions for using maps in their classes.